HER2 IHC Expression and Gene Amplification in p53-aberrant High-grade Endometrial Endometrioid Carcinoma Suggests That This Population May Benefit From HER2 Testing and Targeted Therapy. (20th May 2023) - Joehlin-Price, Amy S.; Komforti, Miglena K.; Ladwig, Nicholas R.; Devine, Patrick; Hoyle, Carrie; McCoy, Lauren; Sprague, Cathy; Astbury, Caroline; Hoda, Raza; Chen, Yunn-Yi; Garg, Karuna
Abstract : Among gynecologic cancers, uterine serous carcinoma (USC) has been shown to be human epidermal growth factor receptor 2 (HER2) amplified and trastuzumab has been included in the recent National Comprehensive Cancer Network (NCCN) guidelines for treatment of advanced stage or recurrent USC with HER2 overexpression/amplification. There is limited literature suggesting that a subset of high-grade endometrioid carcinomas with aberrant p53 expression may also be HER2 amplified and these patients could benefit from the addition of targeted therapy. We identified 59 p53-aberrant (mismatch repair proficient) FIGO 3 endometrioid carcinomas of the uterus. HER2 immunohistochemistry was performed in all 59 tumors and HER2 fluorescence in situ hybridization (FISH) was performed in 52 of the 59 cases. Four of the 59 cases were HER2 3+ by immunohistochemistry (6.7%), using the American Society of Clinical Oncology/College of American Pathologists (ASCO/CAP) 2007, 2013, and 2018 criteria. HER2 FISH was performed in 3 of the 4 cases and was amplified in all 3. Nine, 8, and 7 tumors showed 2+ HER2 staining when applying 2018, 2013, and 2007 criteria, respectively, FISH was performed in 7 tumors and none were amplified. An additional 4 cases did not perfectly meet the 2018 ASCO/CAP criteria but were assigned a score of 2+, none were amplified by HER2 FISH. The remaining 42 cases showed 1+ or no staining for HER2, FISH was successfully performed in 38 tumors and none showed amplification. Approximately half of the tumors fulfilled criteria for HER2-low or HER2-very low (10 HER2-low and 20 HER2-very low). Our data shows that a subset of p53-aberrant high-grade endometrial endometrioid carcinoma express HER2 and these patients may benefit from the addition of targeted therapy. The role of targeted therapy in HER2-low gynecologic carcinoma is currently unexplored.